Morphometry applied to commercial Trichogramma spp. mass rearing - Souza, Diego de (2023)
The quality of a natural enemy is measured in different ways, being the size of organisms an important parameter. The adult’s body size is often determined by the length of the posterior tibia, however, the choice of characteristics to be measured must be done carefully, since using only one to estimate the size of organisms can lead to misunderstandings. The factors that directly influence the size of oophagous parasitoids are the number of individuals that develop in a single host and the host size. Thus, the relationship between the host’s egg size and the parasitoid’s size is also an important parameter to be determined for evaluating the quality of a parasitoid. Understanding which factors can influence the host’s egg size is important to produce resources used in the mass rearing of parasitoids. In this study, the size distribution of the parasitoids Trichogramma pretiosum and Trichogramma galloi was evaluated in order to determine which body part best represents the variation in its size. Therefore, specimens were mounted on slides for microscopy, photographed and the photos were used to measure morphological structures. Large and small specimens were separated based on the size span of their morphological characteristics and the best ones were used to represent the size span of the parasitoids. Eggs of the host Ephestia kuehniella were photographed to estimate their size and relate to the largest parasitoids emerged. Also, the effect of temperatures 20ºC, 22.5ºC and 25ºC on the E. kuehniella egg size was evaluated. Based on principal component analysis and discriminant analysis, we concluded that the wing and ovipositor lengths best represent the variation in size of the parasitoids T. pretiosum and T. galloi. Large parasitoids emerge from the host's largest eggs; however, from a large egg the emergence of a large specimen is not guaranteed. The temperatures experienced by the host E. kuehniella during its immature development and in the adult phase affect the size of its eggs, being bigger at a temperature of 20ºC.